Faktor-Faktor Yang Berhubungan Dengan Kunjungan Antenatal Care Di Klinik Pratama Corah Kec Munte Kab Karo Tahun 2023 - Sri Ermaliani Br Bangun; Isyos Sari Sembiring; Ernawati Napitupulu; Titin Suherni; Elnia Elnia; Rizky Andriani (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Children require special attention as the nation's next generation. The World Health Organization stated that the maternal mortality rate worldwide in 2019 was around 295,000 women who died during and after pregnancy and childbirth. The majority (94%) of maternal deaths occur in low and middle income countries (WHO, 2020). At the 2020 National Working Meeting, the maternal mortality rate in Indonesia in 2019 was still 305 per 100,000 live births (Ministry of Health of the Republic of Indonesia, 2020), which is still high when compared to Indonesia's target in the Sustainable Development Goals (SDGs) in 2030, namely 70 per 100,000 live births. (Pusdatin, 2019). The Sustainable Development Goals (SDGs) era began in 2019 with a program to reduce pregnancy-related morbidity and mortality rates, the achievements of which are still very high in the world. The World Health Organization (WHO) projects that every pregnant woman and newborn needs quality care from pregnancy to the postpartum period. Prenatal care in Indonesia plays an important role in providing quality care, because antenatal care includes elements of health promotion, screening, diagnosis and disease prevention. Indonesia is currently one of the 13 countries with the highest proportion of maternal mortality rates in the world. The high maternal mortality rate is caused by complications during pregnancy. According to the World Health Organization (2019), around 287,000 mothers died due to complications during pregnancy and childbirth, such as bleeding 28%, preeclampsia/eclampsia 2%, infection 11%, and indirect causes (2019), obstetric trauma) 5%. Efforts made to minimize and prevent complications during childbirth are to carry out routine pregnancy checks. Antenatal Care (ANC) is a planned program in the form of observation, providing education and treatment for pregnant women to achieve a safe and satisfactory pregnancy and birth. Antenatal pregnancy checks are the frequency of pregnancy checks at existing health facilities, namely doctors, midwives, health centers, hospitals and other private health facilities. Antenatal examinations should be carried out at least four times during pregnancy, namely once in the first trimester, once in the second trimester and twice in the third trimester (Ministry of Health, 2017). Antenatal examination is a follow-up for pregnant women to prepare physically and mentally and save the mother and baby during pregnancy, childbirth and postpartum (Ministry of Health of the Republic of Indonesia, 2018). The importance of pregnancy checks through prenatal examinations, because in general pregnancies proceed normally, but with increasing gestational age it tends to cause dangerous complications (Rukiyah, 2013). Pregnancy checks are important to ensure that the natural process of pregnancy can run normally and continue so that pregnant women have a healthy and safe pregnancy. It is estimated that around 15% to 20% of all pregnant women will experience high risk conditions and obstetric complications that threaten the lives of both mother and fetus if not treated properly. Indonesian Ministry of Health, 2021). OBJECTIVE To analyze the factors related to Antenatal Care Visits at the Corah Pratama Clinic, Munte District, Karo Regency in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. RESULTS There is a relationship between age, knowledge and antenatal care visits at the Corah Pratama Clinic, Munte District, Karo Regency in 2023 and there is no relationship between parity and support from health workers and antenatal care visits at the Corah Pratama Clinic, Munte District, Karo Regency in 2023.